IMPLEMENTATION OF ROOT CAUSE ANALYSIS ON PATIENT SAFETY IINCIDENCE IN HOSPITAL: LITERATURE REVIEW - Alifia, Redina Thara; Dhamanti, Inge (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACT Background: Root cause analysis (RCA) is a process used by hospitals to reduce the level of patient safety incidents. The minimized application of root cause analysis has resulted in inevitable patient safety incidents. Research objectives: